BRCA1 interactors, RAD50 and BRIP1, as prognostic markers for triple-negative breast cancer severity - Katheeja, Muhseena N.; Das, Shankar Prasad; Das, Ranajit; Laha, Suparna (Frontiers in Genetics, 2023)
BRIP1 is one of the major interacting partners of BRCA1 which plays an important role in repair by homologous recombination (HR). This gene is mutated in around 4% cases of breast cancer, however, its mechanism of action is unclear. In this study, we presented the fundamental role of BRCA1 interactors BRIP1 and RAD50 in the development of differential severity in Triple-Negative Breast Cancer(TNBC) among various affected individuals. We showed that in some TNBC lines like MDA-MB-231 the functioning of both BRCA1/TP53 is compromised. Furthermore, the sensing of DNA damage is affected, depicted through the low expression of damage sensing molecule RAD50 and reduced formation of YH2AX foci. Due to less damage sensing capability and low availability of BRCA1 at the damage sites, the repair by HR becomes inefficient leading to more damage. Accumulation of damage sends a signal for over activation of NHEJ repair pathways. Over expressed NHEJ molecules with compromised HR and checkpoint conditions lead to higher proliferation and error-prone repair, which increases the mutation rate and corresponding tumor severity. The severity phenotypes were more in cells having compromised BRCA1-BRIP1 functioning. The in silico analysis of the TCGA datasets with gene expression in the deceased population shows a significant correlation of BRCA1 expression with overall survival (OS) in TNBCs (0.0272). The association of BRCA1 with OS becomes stronger with the addition of BRIP1expression (0.000876**). Since the OS is directly proportional to the extent of severity, the data analysis hints at the role of BRIP1 in controlling the severity of TNBC.